Molecular markers to complement sentinel node status in predicting survival in patients with high‐risk locally invasive melanoma. Issue 3 (4th April 2016) - Rowe, Casey J.; Tang, Fiona; Hughes, Maria Celia B.; Rodero, Mathieu P.; Malt, Maryrose; Lambie, Duncan; Barbour, Andrew; Hayward, Nicholas K.; Smithers, B. Mark; Green, Adele C.; Khosrotehrani, Kiarash
Abstract : Sentinel lymph node status is a major prognostic marker in locally invasive cutaneous melanoma. However, this procedure is not always feasible, requires advanced logistics and carries rare but significant morbidity. Previous studies have linked markers of tumour biology to patient survival. In this study, we aimed to combine the predictive value of established biomarkers in addition to clinical parameters as indicators of survival in addition to or instead of sentinel node biopsy in a cohort of high‐risk melanoma patients. Patients with locally invasive melanomas undergoing sentinel lymph node biopsy were ascertained and prospectively followed. Information on mortality was validated through the National Death Index. Immunohistochemistry was used to analyse proteins previously reported to be associated with melanoma survival, namely Ki67, p16 and CD163. Evaluation and multivariate analyses according to REMARK criteria were used to generate models to predict disease‐free and melanoma‐specific survival. A total of 189 patients with available archival material of their primary tumour were analysed. Our study sample was representative of the entire cohort ( N = 559). Average Breslow thickness was 2.5 mm. Thirty‐two (17%) patients in the study sample died from melanoma during the follow‐up period. A prognostic score was developed and was strongly predictive of survival, independent of sentinel node status. The score allowed classification of risk of melanoma death in sentinel node‐negative patients. Combining clinicopathological factors and established biomarkers allows prediction of outcome in locally invasive melanoma and might be implemented in addition to or in cases when sentinel node biopsy cannot be performed. Abstract : What's new? Sentinel lymph node status is a major prognostic marker in locally invasive cutaneous melanoma. However, this procedure is not always feasible, requires advanced logistics, and carries rare but significant morbidity. In a study based on a cohort of melanoma patients with locally advanced disease, the authors show that the use of clinicopathological factors and established routine and accessible immunohistochemical markers can be combined in a score that is highly predictive of melanoma prognosis. This score remained highly predictive in sentinel lymph node negative patients, suggesting its potential to be applied in a clinical setting immediately.